Emissions and Air Quality Implications of Enabling On-Road Vehicles as Flexible Load Through Widescale Zero Emission Vehicle Deployment in California. Issue 3 (March 2023) - Forrest, Kate; Lane, Blake; Tarroja, Brian; Mac Kinnon, Michael; Samuelsen, Scott
This study assesses the impacts of on-road light- to heavy-duty zero emission vehicle (ZEV) adoption and charging protocols on greenhouse gas emissions for the years 2030 and 2045 in California, and on air quality for the year 2045. Two scenarios are addressed: (1) a "business-as-usual" (BAU) scenario with modest ZEV adoption, and (2) a "carbon neutral" scenario that achieves carbon neutrality by 2045 with proactive ZEV adoption. Electricity load for fueling ZEVs is projected, including electricity fuel for battery electric vehicles and electrolytic hydrogen for fuel cell electric vehicles. This electric load was input into an electric grid dispatch model and electric grid and air quality analyses were conducted. The results revealed that although medium- and heavy-duty vehicles (MHDVs) are projected to have lower total electric load associated with fueling, they will require roughly double the electricity for hydrogen production of light-duty vehicles. For the electric grid scenarios examined, ZEV loads increased peak electricity demand by 3% to 6% in 2030 and 22% to 31% in 2045. MHDV time-of-use and smart charging strategies were equally able to shift charging demand to off-peak times. Higher ZEV loads under the carbon neutral scenario increased natural gas use up to 6% in 2030 and energy storage requirements up to 45% in 2045 compared with the BAU scenario. The analyses also found that achieving carbon neutrality through ZEV adoption had the cobenefit of significantly reducing ground-level ozone and PM2.5 concentrations in key regions of California, providing health savings of approximately 28 billion annually in 2045.